Developing a decision making test for rugby referees - Mohamad Nizam, Nazarudin; Mohamad Razali, Abdullah; Mohd Sofian Omar, Fauzee; Zainal Abidin, Zainuddin (2015)
The main aim of this research was to develop a decision making test for rugby referees (REFDM). REF-DM can used to evaluate infraction detection and correct calls. REF-DM also stimulates referee communication and visual search ability. Each video clip was filmed from the referee’s perspective and taken from real game situations in order to maintain high ecological validity in accordance with naturalistic decision-making theory. REF-DM has high reliability (Internal Consistency = 0.74). REF-DM was tested during rugby sevens tournament in Malaysia (n=132) and the result showed the potential of this instrument in assessing the referees’ ability infraction detection and making the right calls. This developed instrument has been recommended to the Malaysian Rugby Union for nationwide implementation (for rugby referee professional and decision making skills development). It is also suggested that video-based training program are designed to improve referee performance.